Field emission properties of nano-tendril bundles formed via helium plasma exposure with various additional impurity gases - Rongshi Zhang; Shin Kajita; Dogyun Hwangbo; Hirohiko Tanaka; Shuangyuan Feng; Noriyasu Ohno (Materials Research Express, 2023)
Nano-tendril bundles (NTBs) were formed on tungsten via helium (He) plasma exposure with various additional impurity gases, such as neon (Ne), nitrogen (N _2 ), and argon (Ar). The sizes of the NTBs showed different distributions with different additional impurity gases. The field emission property of the NTBs formed with various additional impurity gases was measured. The field-emission property was significantly affected by the morphology of the NTBs, especially the tips of the fibers. In the Ne- and Ar-seeded cases, the NTBs were formed with sharp tips, and the onset electric field for field emission was ∼1 kV mm ^−1 for all the NTB samples. The Ne-seeded samples showed the most rapid increase in the emission current. In the N _2 -seeded case, two types of NTBs were formed. The NTBs were formed with sharp tips when the ratio of N _2 impurity gas was 2.1%. With an increase in the ratio to 3.0% or higher, the fibers of the NTBs became thicker and the tips became rounder. In the Fowler–Nordheim (F-N) plot analysis, the field enhancement factors were approximately 6000–7000 without significant differences, for all NTBs with sharp tips. NTBs with round tips showed totally different field emission property, as the emission current was only several μ A, which is one-tenth of that for the other samples. This suggests that the local morphology of NTBs, especially the geometrical shape of the tips, and not the general size of NTBs, is the main factor in determining the field emission property of NTBs.